Constrains of Charge-to-Mass Ratios on Noncommutative Phase Space - Kai Ma (Advances in High Energy Physics)
Based on recent measurements on the charge-to-mass ratios of proton and antiproton, we study constraints on the parameters of noncommutative phase space. We find that while the limit on the parameter of coordinate noncommutativity is weak, it is very strong on the parameter of momentum noncommutativity, ξ≲1 μeV. Therefore, the charge-to-mass ratio experiment has a strong sensitivity on the momentum noncommutativity, and enhancement of future experimental achievement can further pin down the momentum noncommutativity.